Smooth switching control of air–ground amphibious robot based on EZMP and integrator initial value - Jie Duan; Heming Zhao; Chungui Zhou; Fei Xie; Zhiling Peng; Zhibo Pei; Kaijie Yue (AIP Advances)
In this paper, a novel controller smooth switching strategy is proposed to address the stability problem of the low-cost air–ground amphibious robot under interference, taking into account both the processor’s performance and the flight control algorithm’s design difficulties. First, the control algorithm is split into a basic structure consisting of proportional and integral, and then, a smooth switching strategy with the initial value assigned to the integrator is designed to suppress the output transient during switching. Second, the extend zero-moment point theory, which integrates the variables of the robot pitch angle and the roll angle, is implemented into the control strategy’s switching logic to reduce frequent switching at the threshold. Finally, the efficiency of the proposed control method is verified by comparing it with other control strategies through simulation experiments.